Sanggar Seni Matoh Mime as A Non-Formal Education Forum: Increasing Creativity and Developing Community Potential - Sabri, Indar; Kusuma, Rizqi Fajar; Alfarisi, Salman (STAI Hubbulwathan Duri, 2024)
This study addresses the challenges educational institutions face in fostering students' interest and skills, particularly in the field of pantomime. A major hurdle is the lack of structured extracurricular activities dedicated to this performance art. This research examines the innovative training techniques employed by Sanggar Seni Matoh Mime as a model of non-formal education aimed at enhancing creativity and developing community potential. The study's objective is to analyze the role of Sanggar Seni Matoh Mime as a non-formal educational platform, focusing on how its pantomime programs contribute to creativity and community development. Utilizing a qualitative case study approach, the findings demonstrate that Sanggar Seni Matoh Mime effectively enhances children's creativity and achievements in pantomime. Since 2019, the Sanggar has provided free pantomime training at Bojonegoro Regency's square, with 32 participants, including one kindergarten student, 28 elementary school students, and three junior high school students. Notably, eight participants won at the Bojonegoro Regency level of the National Student Art Competition Festival. These results highlight the significant contribution of Sanggar Seni Matoh Mime to fostering creativity and artistic potential in the community through non-formal education. In conclusion, this research provides new insights into non-formal education methods and their impact, while encouraging further investigation into the broader effects of non-formal education on community development.